EFEKTIVITAS PENGGUNAAN MEDIA PEMBELAJARAN PAPAN SISTEM PERSAMAAN LINEAR DUA VARIABEL TERHADAP PEMAHAMAN SISWA KELAS VIII - Atmadi; Tuhfatul Janan (LPPM Institut Ahmad Dahlan Probolinggo, 2024)
This study aims to determine the effectiveness of the use of learning media board system of linear equations of two variables (SPLDV) on the understanding of 8th grade students. This research was conducted in September 2023, the first week to the third week, located at MTs Miftahul Ulum. In this study, the data normality test was carried out using the shapiro-wilk method where the results showed that the pre-test significance was 0.207 and the post-test was 0.202, which means that the data is normally distributed. Then the normality gain test was conducted to determine the effectiveness of the SPLDV board as a learning media with an average N-gain score of 0.6724 and the average N-gain percent was 63.8823%. Keywords: learning media, spldv, math